A financial stress index for a highly dollarized developing country: The case of Lebanon - Layal Mansour Ishrakieh; Leila Dagher; Sadika El Hariri (Central Bank Review (CBR), 2020)
The aim of this paper is to construct the first comprehensive Financial Stress Index for Lebanon, dubbed the IFEFSI (Institute of Financial Economics Financial Stress Index). This is a broad coincident composite index that includes three different market segments; the banking sector, the equities market, and the foreign exchange and other markets. It is constructed as a continuous real-time measure that quantifies the level of systemic stress by measuring latent conditions. As a metric for financial conditions, the IFEFSI should provide valuable information to macroprudential regulators whose aim is to maintain a smooth and resilient financial system. By using it as a tool to help monitor, identify, and address any potential crisis, they are better equipped to maintain financial and economic stability in Lebanon.
Keywords: G01; G18; G20; E44; E58; 330; Financial stress index; Financial crisis; Lebanon; Economic policy